A survery on platform of secured routing algorithm - Divya, Miss; R. Gobinath, Dr (International Journal of Engineering and Technology, 2018)
This paper describes the characteristics and techniques of Ad Hoc network. Ad Hoc networks are temporary network, set anywhere with-out any need of external infrastructure like wires. The essential premise of this paper is to exchange confidential message over wireless medium without route break and unauthorized eavesdroppers. In recent years, the research of routing protocol for AdHoc network has caused public concern widely. The multi hopping routing protocol has failed to meet the needs of network topology and route restructure. It must also consider the bandwidth and high error rate. The new routing protocol suitable for solving these problems in Ad Hoc network is AODV.Â